PEMEKARAN DAN KONFLIK BATAS WILAYAH DALAM PERSPEKTIF TEORITIK - Jusan Hi Jusuf (Jurnal GeoCivic, 2023)
In discussing the roots of this conflict, several theories will be put forward that will serve as a basis for discussing issues related to this research problem. The theories in question are Boundary Making Theory, Decentralization Theory, Power Theory, and Resistance Theory. Theory of Boundary Making is used as a basis for looking at historical aspects as a determining factor in the occurrence of regional border conflicts even though the tendency of the theory is more on state border conflicts. The theory of power is used in this study because the core problem in border conflicts is a product of regulation. The party that has competence in issuing regulations is the government as the ruler of the state. Meanwhile, resistance theory is used to analyze the phenomena of the resistance movement as a result of domination within a power structure including the state. In this context, these theories are very relevant if they become the basis or basis for analysis of the research problem as the focus of this research.